Measurement of spatial heterogeneity in street restorative perceptions and street refinement design - Yalun Lei; Qingqing Li; Jingwen Tian; Jia Hu; Jixiang Jiang (Scientific Reports)
Abstract Restorative perception of streets is an essential metric for evaluating urban environments and serves as a key indicator of pedestrians’ perspectives on street refinement design. However, restorative perception varies significantly across different streets, necessitating an analysis of these disparities. This study integrates street view data, deep learning algorithms, the MGWR model, and space syntax to analyze spatial heterogeneity in restorative perceptions and optimize street design strategies. Using the random forest (RF) algorithm and restorative component scales (RCS), we assessed residents’ perceptions of street restoration in Shanghai’s Huangpu District. Our analysis identified eight key visual elements influencing perceptions, such as sidewalks, buildings, and walls. Results revealed significant geographic variations, with high-perception areas concentrated around open parks, waterfronts, and well-designed buildings featuring thoughtful amenities. Visual elements like trees and plants were found to significantly enhance restorative perceptions. Moran’s Ι statistics and multiple regression models further revealed spatial heterogeneity and clustering in perceptions, highlighting the importance of location-based planning. Among the regression models, the MGWR model achieved the highest R 2 value (0.615), indicating that variables like trees, roads, sidewalks, and intercepts are particularly sensitive to spatial heterogeneity. Additionally, space syntax analysis underscores the positive impact of complex street networks on accessibility, convenience, and environmental satisfaction. The main contribution of this study is identifying the most effective model through a comparison of multiple regression models, demonstrating the spatial heterogeneity of different visual elements. Based on restorative perception and accessibility coupling assessment, streets in urgent need of rehabilitation were identified. We believe our findings can assist professionals in developing more targeted and effective strategies based on the restorative nature of streets.